DC‐CIK cells derived from ovarian cancer patient menstrual blood activate the TNFR1‐ASK1‐AIP1 pathway to kill autologous ovarian cancer stem cells. Issue 7 (22nd March 2018) - Qin, Wenxing; Xiong, Ying; Chen, Juan; Huang, Yongyi; Liu, Te
Abstract: Ovarian cancer stem cells (OCSCs) are highly carcinogenic and have very strong resistance to traditional chemotherapeutic drugs; therefore, they are an important factor in ovarian cancer metastasis and recurrence. It has been reported that dendritic cell (DC)‐cytokine‐induced killer (CIK) cells have significant killing effects on all cancer cells across many systems including the blood, digestive, respiratory, urinary and reproductive systems. However, whether DC‐CIK cells can selectively kill OCSCs is currently unclear. In this study, we collected ovarian cancer patient menstrual blood (OCPMB) samples to acquire mononuclear cells and isolated DC‐CIK cells in vitro. In addition, autologous CD44+/CD133+ OCSCs were isolated and used as target cells. The experimental results showed that when DC‐CIK cells and OCSCs were mixed and cultured in vitro at ratios of 5:1, 10:1 and 50:1, the DC‐CIK cells killed significant amounts of OCSCs, inhibited their invasion in vitro and promoted their apoptosis. The qPCR and Western blot results showed that DC‐CIK cells stimulated high expression levels and phosphorylation of TNFR1, ASK1, AIP1 and JNK in OCSCs through the release of TNF‐α. After the endogenous TNFR1 gene was knocked out in OCSCs using the CRISPR/Cas9 technology, the killing function of DC‐CIK cells on target OCSCs was significantly attenuated. The results of the analyses of clinical samples suggested that the TNFR1 expression level was negatively correlated with ovarian cancer stage and prognosis. Therefore, we innovatively confirmed that DC‐CIK cells derived from OCPMB could secret TNF‐α to activate the expression of the TNFR1‐ASK1‐AIP1‐JNK pathway in OCSCs and kill autologous OCSCs.